Prospects for Japan-Republic of Korea relation: A possibility analysis based on the external threats - Zhang Jiayi; Zhang Yuchen; Zhao Hongyu (SHS Web of Conferences, 2023)
The relationship between Japan and Korea has complex historical, political, and cultural dynamics, often characterized by tensions and disputes. Influenced by the intervention of the superpowers, these two countries are economically interdependent and politically opposed. Despite the efforts of the Korean leader to improve the trend, the bilateral relationship faces challenges due to unresolved factors such as historical issues, territorial disputes, and war reparations. This paper takes the external threats affecting the cooperation between Japan and Korea as the research object and evaluates the current situation and obstacles to the bilateral relations between Japan and the Republic of Korea by analyzing the impact of actions taken by countries other than Japan and Korea on their domestic governance, economic conditions, foreign policy decisions, military arrangements, and bilateral relations development. Also, this paper prospects favorable conditions for tightening further bilateral communication, and looks forward to the possibilities of future cooperation between the two countries.